2021
DOI: 10.3390/cells10071694
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Synuclein Preformed Fibrils Induce Cellular Senescence in Parkinson’s Disease Models

Abstract: Emerging evidence indicates that cellular senescence could be a critical inducing factor for aging-associated neurodegenerative disorders. However, the involvement of cellular senescence remains unclear in Parkinson’s disease (PD). To determine this, we assessed the effects of α-synuclein preformed fibrils (α-syn PFF) or 1-methyl-4-phenylpyridinium (MPP+) on changes in cellular senescence markers, employing α-syn PFF treated-dopaminergic N27 cells, primary cortical neurons, astrocytes and microglia and α-syn P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…In another recent study described here, PFF gave rise to activated neuroglia, senescent neuroglia and neuronal death ( Verma et al, 2021 ). MPP + or PFF treatment of cultured dopaminergic rat N27 cells caused the cells to express senescence markers, such as reduced levels of Lamin B1 and HMGB1 and increased levels of p16 and p21.…”
Section: Interactions Between α-Synucleinopathy and Neuroglial Senesc...mentioning
confidence: 62%
See 1 more Smart Citation
“…In another recent study described here, PFF gave rise to activated neuroglia, senescent neuroglia and neuronal death ( Verma et al, 2021 ). MPP + or PFF treatment of cultured dopaminergic rat N27 cells caused the cells to express senescence markers, such as reduced levels of Lamin B1 and HMGB1 and increased levels of p16 and p21.…”
Section: Interactions Between α-Synucleinopathy and Neuroglial Senesc...mentioning
confidence: 62%
“…Lamnin B1, HMGB1, and SATB1 were reduced, p21 levels were increased and p16 levels remained unchanged in postmortem PD brains compared to control midbrain tissues. The experimental results from Verma et al (2021) highlights how pathologic α-synuclein instigates simultaneous neuroglial senescence and neuroglial activation that eventually lead to PD-relevant neuronal death.…”
Section: Interactions Between α-Synucleinopathy and Neuroglial Senesc...mentioning
confidence: 99%
“…Alpha-synuclein, a pathological marker of Parkinson disease, is strongly expressed in the nuclei and synapses of neurons and is physiologically assumed to play an important role in synaptic transmission; however, its normal function remains unclear [ 10 , 11 , 95 , 96 ]. In the early stage of Parkinson disease, soluble alpha-synuclein fibrils are thought to exert neurotoxic effects, and they may act as a TLR4 ligand to induce neuroinflammation in microglia and astrocytes, leading to further neurological damage [ 10 , 11 , 95 , 96 , 112 , 113 ]. In animal models, inflammatory changes were observed in astrocytes and microglia in the substantia nigra after the injection of alpha-synuclein into the striatum and prior to pathological changes in the substantia nigra neurons, suggesting that the initial biological response to alpha-synuclein may be TLR4-mediated neuroinflammation [ 114 , 115 ].…”
Section: Dopamine Alpha-synuclein and Tlr4mentioning
confidence: 99%
“…Studies with mice demonstrated the accumulation of senescent astrocytes and microglia following the injection of alpha-synuclein pre-formed fibrils into the brain. MPP + was also shown to stimulate cellular senescence [ 87 ]. Excitingly, paraquat-induced PD symptoms in mice were mitigated by killing senescent cells [ 88 ].…”
Section: Interventional Strategies To Correct Dysfunctional Mqc and D...mentioning
confidence: 99%